KOMPARASI METODE TOPSIS DAN MFEP DALAM PENENTUAN PEMENANG TENDER - Ariska Rohanda Pakpahan; Dwi Indah Safitri; Horainim Sibarani; Puspa Ramadani; Ramainim Deviana Sibarani (semanTIK, 2018)
This study proposes a comparison between the TOPSIS and MFEP methods to get tender winners using the 2014 Distarukim data sample. This study was conducted to determine which method is better between the TOPSIS and MFEP methods in determining the tender winner. Tender Winners are companies that will carry out a job in accordance with a predetermined plan. Where the criteria used in this study are an arithmetic correction, administrative evaluation, technical evaluation, price fairness evaluation, evaluation of qualifications and verification of qualifications. This study took a case study in Distarukim with a sample of data using six alternatives that had different values for each of the criteria. The ranking results of the two methods are different where the results using the TOPSIS method are better because they match the sample data used. Using the TOPSIS method, the results of CV. Doly Prima Jaya as the winner of the tender followed by CV. Fira, CV. Abdi Jaya, CV. Raflindo, CV. Citra Abadi, CV. Zara Diva.Keywords— Comparison, DSS, TOPSIS, MFEP, TenderDOI : 10.5281/zenodo.2528141